Design and synthesis of peptidic partial agonists of human neuromedin U receptor 1 with enhanced serum stability. Issue 18 (15th September 2020) - Takayama, Kentaro; Mori, Kenji; Asari, Tomo; Sohma, Yuko; Nomura, Erina; Sasaki, Yu; Taguchi, Akihiro; Taniguchi, Atsuhiko; Miyazato, Mikiya; Minamino, Naoto; Kangawa, Kenji; Hayashi, Yoshio
Graphical abstract: Abstract: Neuromedin U (NMU) activates two receptors (NMUR1 and NMUR2) and is a promising candidate for development of drugs to combat obesity. Previously, we obtained hexapeptides as selective full NMUR agonists. Development of a partial agonist which mildly activates receptors is an effective strategy which lead to an understanding of the functions of NMU receptors. In 2014, we reported hexapeptide 3 (CPN-124) as an NMUR1-selective partial agonist but its selectivity and serum stability were unsatisfactory. Herein, we report the development of a hexapeptide-type partial agonist (8, CPN-223) based on a peptide (3 ) but with higher NMUR1-selectivity and enhanced serum stability. A structure-activity relationship study of synthetic pentapeptide derivatives suggested that a hexapeptide is a minimum structure consistent with both good NMUR1-selective agonistic activity and serum stability.